Fibrinogen depletion in trauma: early, easy to estimate and central to trauma-induced coagulopathy - Davenport, Ross (BioMed Central, 2013)
Fibrinogen is fundamental to hemostasis and falls rapidly in trauma hemorrhage, although levels are not routinely measured in the acute bleeding episode. Prompt identification of critically low levels of fibrinogen and early supplementation has the potential to correct trauma-induced coagulation and improve outcomes. Early estimation of hypofibrinogenemia is possible using surrogate markers of shock and hemorrhage; for example, hemoglobin and base excess. Rapid replacement with fibrinogen concentrate or cryoprecipitate should be considered a clinical priority in major trauma hemorrhage.